Adoption of e-Wallet among University of Malaya students / Tan Jia Enn - Tan , Jia Enn (2020)
Malaysia is towards a cashless nation and factors that delaying the process of cashless society are still unclear. The objective of this paper is to examine the adoption of e-wallet among University of Malaya (UM) students. The purpose is examined by key determinants which include social influence, perceived ease of use, perceived usefulness, perceived security and trust among university students. Data is collected by a self-administered survey questionnaire from University of Malaya (UM) students. Software IBM SPSS is adopted to analyse the data collected from survey questionnaires. The findings in this study shows that social influence and perceived usefulness are a significant determinant towards adoption of e-wallet. While, perceived ease of use, perceived security and trust are not an important determinant on adoption of e-wallet.